Prescriptions for Mitigating Climate Change–Related Externalities in Cancer Care: A Surgeon's Perspective. Issue 18 (20th June 2022) - Agbafe, Victor; Berlin, Nicholas L.; Butler, Charles E.; Hawk, Ernest; Offodile II, Anaeze C.
Abstract :